Influence of biologics on carbohydrate metabolism and risk of diabetes - L. V. Kondratieva; T. V. Popkova; E. L. Nasonov (Научно-практическая ревматология)
In the article the analysis of the literature on the impact of biologics of different groups (inhibitors of tumor necrosis factor α, tocilizumab, abatacept, rituximab and interleukin 1 inhibitors) on the production of insulin by the pancreas, insulin resistance and the risk of development of the 2nd type diabetes in patients with rheumatic diseases.